1994
DOI: 10.1055/s-2007-1021113
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic Force-Velocity Curves in Patients Following Implantation of an Individual Total Hip Prosthesis

Abstract: There are only a few studies which could support conclusions concerning the strength of the muscles surrounding the hip joint and especially concerning the strength relationships following implantation of endoprostheses. The aim of this study was to examine the post-operative course of strength deficits in this musculature compared to clinical parameters. Fifty-eight patients between 30 and 67 years of age, in whom individual total hip prostheses were implanted, were clinically examined prior, 9 weeks and 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
2
12
1
Order By: Relevance
“…This defi cit in strength was most likely a result of the disease process of hip OA and a reduction in muscle activity. We thus believe that previous studies using preoperative strength 5,6,8,9) or uninvolved side strength 2,5-7) as a reference value may have overestimated the postoperative recovery of muscle strength.…”
Section: Discussionmentioning
confidence: 87%
“…This defi cit in strength was most likely a result of the disease process of hip OA and a reduction in muscle activity. We thus believe that previous studies using preoperative strength 5,6,8,9) or uninvolved side strength 2,5-7) as a reference value may have overestimated the postoperative recovery of muscle strength.…”
Section: Discussionmentioning
confidence: 87%
“…Published investigations documenting torque production of the hip joint musculature before hip arthroplasty are limited (10,16,18,20,22). In fact, there are limited studies focusing on the torque-producing ability of the extensors (3, 10, 18) and flexors (3,10,18,20) before THA. Concerning the hip extensors, Horstmann and colleagues reported that an individual before THA generated 52% of the torque produced on the uninvolved side before total hip surgery tested isokinetically at 60Њ·sec Ϫ1 (10).…”
Section: Discussionmentioning
confidence: 98%
“…Isokinetic strength has been successfully used in another published investigation to assess an individual's ability to produce torque of the hip joint musculature (10). In the present study, we used a Cybex (Henley Health Systems, Sugarland, TX) isokinetic system to assess torque production of the hip extensors and flexors before and 60 days after surgery.…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%
See 2 more Smart Citations